THE EXPANSION OF HIGHER EDUCATION - KLEINBERGER, A.F. (Pedagogische Studiën, 1969)
this paper I shall attempt to analyse some of the problems involin the rapid expansion of higher education which has been goingn many countries since the end of the Second World War, and in’he still more rapid expansion which is being envisaged or’ projected in’’lany countries for the next decade or two. For lack of competency I^hall not deal with the economic and financial aspects of the topic,although their crucial importance for any policy of educational expan^’on is of course beyond dispute, and they have attractcd the serious®’’ention of scholars and policymakers alike. The analysis will be baon comparison of actual or projected developments in the field of^’gher education in a number of European and nonEuropean coun’fies which, in respect of their economies and systems of formal educa^’on, are counted among the relativcly developed nations. These coun^’’ies have been selected not only on account of significant developmentsbe observed in their higher educational systems but also because daand literature concerning such developments have been more readily®ccessible to the author. This more or less arbitrary selection should. y no means be taken to imply that phenomena of equal import and"iterest could not have been recorded in ether countries as well,ßet’ore broaching our subject, a few preliminary remarks are indicaconcerning the definition of the term „higher education", or ratherdemarcation of the field denoted by that term. There are four prin^’Pal approaches todefininc our concept which, thoi.gh not by necessi’y niutually cxclusive, result in different ranges of application for thatConcept which, it is true, overlap to a considerable extent but are by no"’eans congruent.